Antidiabetic Activity Test of Fe(III) Complex Compound with Arginine Ligand in Male Mice (Mus Musculus L.) - Yuli Ambarwati; Nurhasanah Nurhasanah; Nisa Karima; Hari Purnomo (Journal of Multidisciplinary Applied Natural Science, 2025)
Diabetes mellitus is characterized by high blood sugar levels in the body. Treatment for type 1 diabetes mellitus is with insulin injections while treatment for type 2 diabetes mellitus generally uses oral medication. Currently, people are looking for diabetes drugs made from complex compounds using metals. The development of research and utilization of Fe(III) complex compounds is still limited, thus, in this study the synthesis of Fe(III) complex compounds with arginine ligands was carried out. The results of the research obtained a complex compound of Fe(III)-arginine with 96%, in the form of a brown gel with a sample weight of 0.5601 g. Characterization using a UV-Vis spectrophotometer showed absorption at a wavelength of 203 nm which indicated the absorption of the Fe(III)-arginine complex. The results of FTIR analysis showed a typical absorption of Fe–O and Fe–N bonds at a wavelength of 500–600 nm. The results of the calculation of the mice's body weight decreased when induced by alloxan. After 3 and 4 weeks, the mice's body weight returned to stability. The highest decrease in glucose levels was in dose 2, namely 100 μg/kg bw with a decrease in %GL of 66.72%. The results of this study show that the complex compound Fe(III) arginine can reduce blood glucose levels in mice.